Long non-coding RNAs MACC1-AS1 and FOXD2-AS1 mediate NSD2-induced cisplatin resistance in esophageal squamous cell carcinoma - Wenhua Xue; Zhibo Shen; Lifeng Li; Yuanyuan Zheng; Dan Yan; Quancheng Kan; Jie Zhao (Elsevier, 2021)
The nuclear receptor-binding SET domain (NSD) protein family encoding histone lysine methyltransferases is involved in cancer progression. However, the role of NSDs in esophageal squamous cell carcinoma (ESCC) remains unclear. Here we examined the expression of NSDs in cisplatin-resistant and parental ESCC cells and revealed the upregulation of NSD2 in cisplatin-resistant cells. Ectopic expression of NSD2 increased cisplatin resistance and attenuated cisplatin-induced apoptosis. Colony formation assay indicated that NSD2 overexpression enhanced long-term survival of ESCC cells after treatment with cisplatin. In contrast, knockdown of NSD2 inhibited ESCC cell proliferation and sensitized ESCC cells to cisplatin. Depletion of NSD2 augmented the cytotoxic effect of cisplatin on EC109 xenograft tumors. NSD2 stimulated long non-coding RNA MACC1-AS1 in ESCC cells. Knockdown of MACC1-AS1 impaired NSD2-induced cisplatin resistance. Moreover, MACC1-AS1 overexpression promoted ESCC cell proliferation and cisplatin resistance. Clinically, MACC1-AS1 was upregulated in ESCC relative to adjacent noncancerous tissues. High MACC1-AS1 levels were significantly associated with reduced overall survival of ESCC patients. There was a positive correlation between MACC1-AS1 and NSD2 expression in ESCC specimens. Taken together, MACC1-AS1 induced by NSD2 mediates resistance to cisplatin in ESCC and may represent a novel target to improve cisplatin-based chemotherapy.